Analisis desain kapal ikan multifungsi 10 GT bertenaga hybrid dengan memanfaatkan energi terbarukan dan motor diesel di perairan Sulawesi Tenggara - Djunuda, Rahmawati; Aras Mubarak, Azhar; Samaluddin, Samaluddin; Muhaimin, Abdul; Hariyono, Hariyono (Jurnal Ilmiah Giga, 2024)
Fishermen operating in the waters of Southeast Sulawesi typically use fishing vessels powered by diesel engines. Additionally, the onboard basic electrical needs are met using batteries that must be manually charged, leading to increased time, costs, and workload for the fishermen. Given the vast potential of the region, an in-depth analysis is needed to explore the integration of renewable energy with diesel engines to better support local fishermen. This study aims to develop a design for a 10 GT multifunctional fishing vessel that incorporates a hybrid power system, utilizing solar energy as an alternative electrical energy source in combination with a diesel engine. The creation of this multifunctional vessel design will enable year-round operation by adapting to seasonal changes in Indonesia while maintaining high-quality catch production. The research findings indicate that a 10 GT fishing vessel with a length of 15 meters, width of 5 meters, and a draft of 0.75 meters can be equipped with a 40 PK diesel engine and a 60-volt electric outboard motor. The Compton method yielded a resistance of 9.8 kN and a power requirement of 50.5 kW. The Fung method calculated a resistance of 6.5 kN and a power of 33.3 kW, while the Holtrop method produced a resistance of 5.3 kN and a power of 27.4 kW. The proposed solar energy system for the vessel includes six solar panels, each with a capacity of 250 WP, providing power for both the ship's engine and onboard electrical equipment.